A Normative Argument Towards the Independence of Public Debt Management - Tsintzos, Panagiotis; Efthimiadis, Tilemahos; Papadamou, Stephanos; Spyromitros, Eleftherios (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2023)
We explore the links between credit expansion, inflation, and inflation expectations, and show that active public debt management can trigger a non-interest rate channel of credit expansion. This creates incentives for the government to use debt management for promoting non-debt management goals, thus, choosing debt maturity structure that differs from its optimal. Through a theoretical monetary policy game, we show that it is welfare improving to delegate public debt management to an independent office separate from the fiscal authority.